Factors Affecting Safety Action in JOB Pertamina-Medco E&P Tomori Sulawesi - Harjanto, Meddy; Djunaidi, Zulkifli (National Journal of Occupational Health and Safety, 2020)
Increasing oil and gas production is one of the main concerns for companies engaged in oil and gas mining Human behavior related to safety is an approach to analyze what is needed to make the safe action more possible and reduce risky behavior. Therefore, research is conducted on the factors that influence safe behavior so that these factors can be more optimized. This research is a quantitative study with a cross-sectional design. The population in this study amounted to 291 people. Data retrieval is done randomly with a sample of 130 respondents conducted using the simple random sampling method. Bivariate analysis was carried out by the chi-square test. Based on the results of the study, it was found that 63.8% of workers behaved safely, and 36.2% of workers behaved unsafely. Factors that do not affect safe behavior are knowledge, attitude, perception, motivation, age, length of work, availability of PPE, safety regulations, safety promotion, and training. Whereas, the factors that are proven to influence safe behavior are the supervisory role and the role of co-workers. Therefore, the researcher suggested that supervisors play an active role and be monitored regularly and consistently. In addition, care for co-worker needs to be improved through the Safety Observation program.